Supplemental methionine selenium effects on egg yolk physicochemical, functional, and protein structure during storage - Chen, Dan; Liu, Yaotong; Xu, Shiwen (Frontiers in Nutrition, 2023)
Mixing different forms of selenium products into chicken feed can significantly improve the shelf life of eggs. However, there is relatively little research on the changes in the yolk of selenium-rich eggs during storage. Therefore, we investigated the changes in the physicochemical properties, functional characteristics, and protein structural characteristics of egg yolks during 28 days of storage at 4 ℃ and 25 ℃. The results showed that during storage at 4 ℃ and 25 ℃, the range of water content changes in the C-group was 47.17 48.70% and 47.17 49.80%, respectively, with pH values ranging from 5.99 to 6.01 and 5.99 to 6.26, respectively. The range of water content changes in the Se group was 46.88 48.21% and 46.88 50.06%, respectively, with pH values ranging from 5.97 to 6.03 and 5.97 to 6.23. Rheology results show that the decrease in the apparent viscosity of samples in the Se-Group is smaller than that in the C-Group. The absolute decrease in the zeta potential of the Se group was lower than that of the C group. The results of functional properties showed that the hardness and chewiness in the Se group were lower than those in the C group, and the antioxidant capacity and emulsification were better than those in the C group. The protein structure results show that the degree of order and fluorescence intensity of egg yolk proteins in the Se group are higher than those in the C group, and the Se group has a higher abundance of polymer proteins. Therefore, the addition of methionine selenium can reduce the degree of egg yolk fission during storage and extend its shelf life.